AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DI DESA BATU BELAH KECAMATAN SIANTAN TIMUR KABUPATEN KEPULAUAN ANAMBAS - Yogi Saputra; Salihi Salihi; Afriyadi Afriyadi (Juremi: Jurnal Riset Ekonomi, 2023)
Village fund allocations in Batu Belah Village, East Siantan District, Anambas Islands Regency, especially in 2021 including planning, implementation, reporting and accountability indicators. In this study, the authors used qualitative research. The results of this study showed that the village government has implemented transparency and accountability, this can be seen from the three indicators of planning, implementation, reporting and accountability of Village Fund management. It's just that, there are several obstacles related to implementation in the field of development, one of the obstacles encountered is uncertain weather, delays in raw materials sent from outside the village and constraints on administering village officials, butnot fatally interfering with the performance of the Batu Belah village government, Siantan District East Anambas Islands Regency